Effect of stratospheric conditions on germination and seedlings of olanum lycopersicum "tomato prince borghese" and beta vulgaris "beet" - Dueñas-Parapar, Diego (2024)
The stratosphere is a layer of the Earth’s atmosphere, located above the anthroposphere and below the mesosphere. The stratosphere has particular meteorological conditions, such as high UV-A radiation, slow atmospheric pressure, and temperature variations. Currently, several studies have shown that organisms suchas plants can be positively affected by exposure to stratospheric conditions, especially UV-A radiation. However, studies on the viability of seeds have been little developed. For this reason, this study aimed to evaluate the viability of Solanum lycopersicum Lam, 1794 “Tomato Prince Borghese” and Beta vulgaris Linneo, 1753 “Beet” seeds under stratospheric conditions. Th e seeds were taken to the stratosphere by the stratospheric balloon of the “Asociación Peruana de Astrobiología”, which is also equipped with meteorological instruments to measure the altitude, temperature, atmospheric pressure, and UV-A radiation present from launch to the return of the sample. Seed viability has been determined based on a comparative analysis of germination and early stem and root elongation of seeds exposed to stratospheric and unexposed conditions. The main results show that stratospheric conditions increase signifi cantly stem elongation in S. lycopersicum and total weight in both species. This research presents interesting results for the study of techniques for the rapid germination and development of crops.